Population Ageing, Public Health Expenditure and the Primary Fiscal Balance: Evidence from a Heterogeneous Global Panel, 1990–2024 - Ha Thi Doan Trang; Vu Ngoc Dung (Economies, 2026)
Evidence on the fiscal consequences of population ageing rests largely on projections and regional panels. We examine how ageing relates to growth and the primary fiscal balance across sixty-nine economies from 1990 to 2024. Because cross-sectional dependence is pervasive and slope homogeneity rejected, inference rests on outlier-robust common correlated effects and augmented mean-group estimators, with system generalised method of moments (GMM) used as a robustness check. First, ageing has no robust average effect on growth or the balance once slopes differ and common global movements are removed, and no convex fiscal profile survives. Second, the fiscal cost of ageing is concentrated in economies at earlier stages of the demographic transition, where a one-point rise in old-age dependency is associated with a primary balance weaker by about 1.2 percentage points of GDP, an ordering that survives every specification we estimate. Third, publicly financed health care carries that weight: one percentage point of GDP of such spending is associated with a balance weaker by 1.5 to 1.9 percentage points, while privately financed care shows no such association. The demographic push on that spending is itself weakly estimated and appears only with a lag. Containing such spending requires building health-financing and revenue capacity during the transition.